(untitled) (Physical Education, Health and Social Sciences, 2026)
The composite of metal organic framework have gained much attention in the biological field due to their porous nature and enhance biological activity. In the first step of the current study zinc oxide nanoparticles was prepared and in the second step zinc based carboxylic acid metal organic framework (Zn-BTC) was prepared using precipitation method. At the last step the zinc oxide nanoparticles have been incorporated into zinc based carboxylic acid metal organic framework (Zn-BTC) using UV irradiation method. The synthesised samples was characterized using Scanning electron microscopy and energy dispersive x-ray and then the samples were used for the inhibition of alpha amylase and alpha glucosidase enzymes. The IC50 values for ZnO, Zn-BTC and zinc oxide incorporated Zn-BTC for alpha amylase was found to be 7.01 ±0.064, 8.06± 0.054 and 5.89± 0.083, respectively. Further the IC50 values for ZnO, Zn-BTC and zinc oxide incorporated Zn-BTC for alpha glucosidase was found to be 11.06 ±0.053, 8.02± 0.045 and 10.87± 0.087 respectively.